Could urban greening mitigate suburban thermal inequity?: the role of residents' dispositions and household practices. (26th September 2016) - Byrne, Jason; Ambrey, Christopher; Portanger, Chloe; Lo, Alex; Matthews, Tony; Baker, Douglas; Davison, Aidan
Abstract: Over the past decade research on urban thermal inequity has grown, with a focus on denser built environments. In this letter we examine thermal inequity associated with climate change impacts and changes to urban form in a comparatively socio-economically disadvantaged Australian suburb. Local urban densification policies designed to counteract sprawl have reduced block sizes, increased height limits, and diminished urban tree canopy cover (UTC). Little attention has been given to the combined effects of lower UTC and increased heat on disadvantaged residents. Such impacts include rising energy expenditure to maintain thermal comfort (i.e. cooling dwellings). We used a survey of residents ( n = 230) to determine their perceptions of climate change impacts; household energy costs; household thermal comfort practices; and dispositions towards using green infrastructure to combat heat. Results suggest that while comparatively disadvantaged residents spend more on energy as a proportion of their income, they appear to have reduced capacity to adapt to climate change at the household scale. We found most residents favoured more urban greening and supported tree planting in local parks and streets. Findings have implications for policy responses aimed at achieving urban climate justice.